An Endochronic Constitutive Law for Static Shear Behavior of Overconsolidated Clays - Imai, Goro; Xie, Chanjuan (SOILS AND FOUNDATIONS, 1990)
Based on the endochronic theory, constitutive relations for overconsolidated clay subjected to static loading have been obtained. The constitutive relations expressed in a closed form can generally describe both deviatoric shear responses and pore pressure responses including negative responses induced by dilatancy. The model further can account for the effect of effective confining pressure on the responses, strain hardening and softening behaviors, dilatancy behaviors, and the effect of overconsolidated ratio, OCR, on the responses. The model is applied to describe the undrained simple shear test data on Boston Blue clay (Ladd and Foott, 1974) and undrained triaxial compression tests on Shanghai clay as well as South Sea clay carried out by the second author. It is shown in this paper that the model yields a reasonable description for the mechanical behaviors of overconsolidated clays subjected to static loading.